(untitled) (Research, Society and Development, 2020)
Introduction: In the hospital context, food and nutrition are responsible for restoring patients’ health, providing the essential and adequate supply of nutrients. Objective: To analyze the profile of human resources in their health services and to be involved in the context of food safety in hospital production units in the city of Aracaju, Sergipe. Method: A semistructured questionnaire was applied, seeking information on the characterization of the functional organization and human resources of the evaluated units. The professor was approved by the Research Ethics Committee of the Federal University of Sergipe. There were 211 employees, a majority female, with a high school. Results: All units of functional units have the necessary capacities and training with employees. However, as companies demonstrated difficulties in hiring employees in varied positions, these were related to lack of experience, technical knowledge and professional qualification. Conclusion: It was observed that most of the employees did not have courses in the area in which they work. For the minimun that deficiency, see must the capacity of training and capaciting, a strategy and low cost of, low provision, the continuous actions of the way continuous.